Compatibilism and Incompatibilism in Social Cognition. (25th March 2016) - Turri, John
Abstract: Compatibilism is the view that determinism is compatible with acting freely and being morally responsible. Incompatibilism is the opposite view. It is often claimed that compatibilism or incompatibilism is a natural part of ordinary social cognition. That is, it is often claimed that patterns in our everyday social judgments reveal an implicit commitment to either compatibilism or incompatibilism. This paper reports five experiments designed to identify such patterns. The results support a nuanced hybrid account: The central tendencies in ordinary social cognition are compatibilism about moral responsibility, compatibilism about positive moral accountability (i.e., about deserving credit for good outcomes), neither compatibilism nor incompatibilism about negative moral accountability (i.e., about deserving blame for bad outcomes), compatibilism about choice for actions with positive outcomes, and incompatibilism about choice for actions with negative or neutral outcomes.